Antiplatelet drugs and liver fibrosis. (17th February 2022) - Czajka, Pamela; Przybyłkowski, Adam; Nowak, Anna; Postula, Marek; Wolska, Marta; Mirowska-Guzel, Dagmara; Czlonkowska, Anna; Eyileten, Ceren
Abstract: Liver fibrosis results from an imbalance between extracellular matrix formation and degradation. The background of liver fibrosis is chronic inflammation and subsequent microcirculation disturbance including microthrombosis. Platelets actively participate in liver fibrosis not only as a part of the clotting system but also by releasing granules containing important mediators. In fact, platelets may play a dual role in the pathophysiology of liver fibrosis as they are able to stimulate regeneration as well as aggravate the destruction of the liver. Recent studies revealed that antiplatelet therapy correlates with inhibition of liver fibrosis. However, liver impairment is associated with extensive coagulation disorders thus the safety of antiplatelet therapy is an area for detailed exploration. In this review, the role of platelets in liver fibrosis and accompanying hemostatic disorders are discussed. Additionally, results of animal and human studies on antiplatelet drugs in liver disorders and their potential therapeutic utility are presented.